Construction and Reflection of Androgynous Gender in Discourse “A Study of Unique Discursive Practices of Hijra Community of Lahore, Pakistan” - Neelam Nazir (Journal of Peace, Development and Communication, 2021)
This study is an attempt to shed some light on the distinctive discursive practices of the Hijra (eunuch or hermaphrodite) communities located mostly if not all in the suburb of Lahore. These discursive practices serve as a source to construct and reflect their androgynous gender on different levels of their social discourse, ultimately helps us to identify how they understand reality around them, construct their identities and negotiate their roles as Hijras. A sample comprised 25 members of the hijra communities was selected to investigate what kind of discursive practices they carry out in their everyday interaction within their communities. The data was elicited through interviews and observations of the target communities. The results show that their unique discursive practices, in many ways different from others are characteristics of their group formation such as chandni dera, rawana dera, and arrwana daira. They communicate through a vernacular dialect of Punjabi, may be labeled as hijra vernacular. Their community of practices cover registers (e.g., khol for home, luri for girl, khondi for mother, santla for clothes, jog for hair and so on) are exclusive to them. They prefer to use highly contextual masculine and feminine pronouns (e.g. mera guru sahib for my teacher, meri behan for my sister and, mera beta for my son) to mark their group formation. Gender is not a fixed category for hijras and they use masculine and feminine pronouns according to the masculine or feminine roles assigned to them in their groups. Keywords: Hijra, Eunuch, Discursive Practices, Discourse Analysis and Gender